IMPROVING ABILITY TO SPEAK MOTHER TOUNGE THROUGH USE OF MINANGKABAU CREATION - Yetti Yetti; Vivi Anggraini; Hapidin Hapidin (Program Pascasarjana Universitas Negeri Jakarta, 2017)
This study aims to describe the process and learning outcomes through the use of song creation Minangkabau in improving the ability to speak the child's mother. This research is conducted in TK Nurul Hidayah., Bukittinggi- West Sumatra in January until February 2017. The subjects were students group B were 17 children. This study uses research methods Action research, from comprising: a) planning, b) actions and observations, c) reflection. Conducted over 16 sessions that are divided into two cycles. Data was collected through tests, observations, interviews and documentation study. Data analysis techniques used in this research is the analysis of qualitative and quantitative data. Quantitative data analysis used to determine the percentage of children's ability to speak their mother tongue after the action. the results showed an increase in children after learning to use the song Minangkabau creations. pre-actions are performed to determine the percentage of children's mother tonge by 47, 43%, increased to 68.38% after the cycle for the First, and increased to 87, 50% after the second cycle. The ability to speak their mother tongue can be developed through the use of song creation Minangkabau, where the song creations Minangkabau can attract children to use their imagination so that he is able to express ideas. Minangkabau creations song is a fun activity for young children.